Parental compliance with therapy home programmes within a school for learners with special educational needs : an exploratory study - Melling-Williams, Natalie (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Rehabilitation))--University of Stellenbosch, 2005.